Anterior uveitis as an early diagnostic marker in incomplete Kawasaki disease - Kyung Ok Ko; Eun Jung Cheon (BMC, 2024)
Abstract Background Kawasaki disease (KD) is a significant cause of acquired heart disease in children, particularly in developed countries. Incomplete Kawasaki disease (IKD) lacks some of the classic KD symptoms, complicating diagnosis. This study explores the potential role of anterior uveitis (AU) as a diagnostic marker for IKD and its possible association with reducing the incidence of coronary artery lesions (CALs). Methods A retrospective review of medical records was conducted on 111 pediatric patients diagnosed with IKD at two tertiary care centers between January 2018 and December 2023. The cohort consisted of 33 patients with AU and 78 without AU. The AU group had a mean age of 4.1 years, while the non-AU group had a mean age of 4.5 years. AU was present in 30% of cases. The study primarily focused on the time to diagnosis, incidence of CALs, and the independent association of AU with CALs using multivariate logistic regression analysis. Results Patients with AU were diagnosed and treated earlier, with a mean time to diagnosis of 5.1 days compared to 7.4 days in the non-AU group. Additionally, the incidence of CALs was significantly lower in the AU group (4.4%) compared to the non-AU group (31.8%, p < 0.001). Multivariate analysis revealed that AU was independently associated with a significantly reduced risk of CALs (OR = 0.066, 95% CI = 0.009-0.494, P = 0.008). Conclusions This study suggests that AU may be associated with earlier diagnosis and treatment of IKD, potentially lowering the risk of CALs. While AU shows promise as a diagnostic marker, further prospective studies are needed to validate these findings and determine whether AU should be integrated into clinical guidelines for earlier detection of IKD and improved patient outcomes.